A study comparing SPECT with CT and MRI after closed head injury. - Newton, M R (1992)
After closed head injury nineteen patients had single photon emission tomography (SPECT) using the lipophilic tracer 99m-Technetium hexamethyl-propylene-amineoxime (HMPAO) to compare the defects shown by CT and MRI. SPECT showed more focal cerebral lesions than either CT or MRI alone or in combination. Most lesions shown by SPECT were not shown by CT or MRI in the corresponding anatomical regions. The most severely disabled patients showed the highest number of SPECT lesions (average four per patient) and the lowest (mean, SE) cerebral blood flow (718, 69 ml/min) compared with the less disabled patients (two per patient and 1058, 51 ml/min, p less than 0.05). There was a correlation between the Glasgow Outcome Scale grade and the global cerebral blood flow (r 0.74, p less than 0.05). The perfusion defects may correlate with clinical signs that were not explained by CT or MRI findings. SPECT may complement the clinical evaluation in the assessment of outcome after head injury.